Training software for orthogonal packing problems. (September 2017) - Costa, Gianluca; Delorme, Maxence; Iori, Manuel; Malaguti, Enrico; Martello, Silvano
Highlights: An open source architecture is presented. It allows interactive solution of two-dimensional packing problems. It was tested by engineering students. We report the results of classroom experiments. Abstract: An open source architecture for the interactive solution of packing problems in two dimensions is presented. Although primarily developed for helping engineering students to understand the algorithmic approaches to the solution of difficult combinatorial optimization problems, the application can be useful to practitioners and developers thanks to its visual tools. The paper gives intuitive and formal definitions of the problems at hand, discusses two natural heuristic approaches, provides technical information on the application, and reports the results of classroom experimental testings.